2000
DOI: 10.1111/1467-7687.00123
|View full text |Cite
|
Sign up to set email alerts
|

Preverbal children with autism understand the intentions of others

Abstract: There is a`theory of mind' theory of autism. Meltzoff has recently developed a procedure that gives a nonverbal assessment of`theory of mind'. A group of children with autism and a matched control group of normally developing infants were given three of Meltzoff's tasks and three conventional, gestural imitation tasks. The children with autism showed the expected deficits on gestural imitation, but were significantly better than the normally developing infants on the Meltzoff tasks. The implications of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 4 publications
6
89
1
Order By: Relevance
“…Also other studies report few difficulties with intention understanding in children with ASD (e.g., Aldridge et al, 2000;Carpenter et al, 2001). …”
Section: Intention Understanding 23mentioning
confidence: 88%
See 1 more Smart Citation
“…Also other studies report few difficulties with intention understanding in children with ASD (e.g., Aldridge et al, 2000;Carpenter et al, 2001). …”
Section: Intention Understanding 23mentioning
confidence: 88%
“…Given the disturbed ability to infer mental states of others in children with ASD (e.g., Happé, 1995; Baron-Cohen, Leslie, & Frith, 1985;Yirmiya, Erel, Shaked, & Solomonica-Levi, 1998), it is plausible that they also experience problems with the easiest forms of mental states, such as intentions. However, studies that have investigated intention understanding in children with ASD, report contrasting results (e.g., Aldridge, Stone, Sweeney, & Bower, 2000;Carpenter, Pennington, & Rogers, 2001;d'Entremont & Yazbek, 2007), possibly due to different paradigms. Moreover, these studies were conducted with somewhat older children, at an age when intention understanding is typically robustly achieved.…”
mentioning
confidence: 99%
“…In three studies group differences on gestural imitation were of a greater magnitude than these on procedural imitation (DeMeyer et al 1972;Roeyers et al 1998;Stone et al 1997). The research group of Aldridge et al (2000) concluded that mentally impaired preschoolers with autism were poorer on bodily imitation, but better on procedural imitation than mental age matched typically developing infants (Aldridge et al 2000). Contrarily, Rogers et al (2003) found in toddlers with autism, compared to both typically developing and developmentally delayed peers, impairments in facial and procedural imitation, but not in gestural imitation (Rogers et al 2003).…”
mentioning
confidence: 99%
“…In addition, the presence of the objects could potentially evoke a number of non-imitative behaviours, such as replication of skilled acts (Aldridge et al 2000;DeMeyer et al 1972;Stone et al 1990). All studies have used imitation tests without normative data.…”
mentioning
confidence: 99%
“…There are indications that in children with ASD the mimicry pathway is more limited than the emulation/planning pathway [23]. In other words, if the goal or function of the behaviour is clear the modelled behaviour is more likely to be emulated and the goal/function is more likely to be achieved without necessarily reproducing the topography of the behaviour [25,26]. On the other hand, if the goal/function of the behaviour is not clear the behaviour is generally less likely to be mimicked [27,28].…”
mentioning
confidence: 99%